VALUE CHAIN, KAIN ULOS DAN ULAON UNJUK ADAT BATAK TOBA - Naibaho, Dameria; ., Ratna (UP2M SEKOLAH TINGGI ILMU EKONOMI GALILEO, 2018)
âUlaon Unjukâ is a traditional Batak Toba Wedding Ceremony. If taker too much time, all day long, even over 6 p.m . this leads to extra expense for renting hall, and in village even spends longer, till 9 p.m. In this ceremony, brideâs family, relatives and colleagues give the couple âUlosâ , totally hundreds, these âulosâ when resell , the price decrease more than 70% from the normal price. This research is aimed at finding out the value chain of âulosâ used in Batak Toba traditional wedding ceremony in Sumatera Utara Province. Specifically, finding out activities, value, and act evaluation, in value chain of âUlosâ. Respondents are âUlosâ weavers and sellers, with responsive rate 90,91%, cultural regulators, Brideâs families, Â and guests with responsive rate 90,28%. Respondents are from Medan City and Pematang Siantar City. Data needed are function and value of âUlosâ, preparing and offering âUlosâ in âUlaon Unjukâ. Data collected by applying opened-qualitative method, which then, are tabulated and analyzed qualitatively. The result shows that 60% of the respondents mentioned that âUlosâ offering would be better given in form of money (as âULOS NATINONUN SADARIâ). It will decrease time and leads to no extra expense and keeps the normal price of ulos.Kata KunciÂ Â Â Â Â : Ulaon Unjuk (Batak Toba Traditional Wedding Ceremony), Kain Ulos (Batak Traditional Cloth), Ulos Holong (âUlosâ given by Brideâs families, relatives and colleagues), and Value Chain